Alloimmune Responses and Atherosclerotic Disease After Kidney Transplantation. Issue 1 (January 2015) - Ducloux, Didier; Courivaud, Cécile; Bamoulid, Jamal; Bisaccia, Vincent; Roubiou, Caroline; Crepin, Thomas; Gaugler, Béatrice; Laheurte, Caroline; Rebibou, Jean-Michel; Chalopin, Jean-Marc; Saas, Philippe
Abstract : Background: Chronic exposure to exogenous antigens causes accumulation of proinflammatory CD57 + CD28 − hyperactivated CD8 + T cells that may promote atherosclerosis. We hypothesized that persistent alloimmune responses may induce immune activation and contribute to posttransplant atherosclerosis. Methods: This hypothesis was tested in a single-center cohort of 577 kidney transplant patients. Propensity score analysis was performed to address potential confounding variables by indication. Immune exhaustion was studied in subcohort of 103 patients. Results: Five hundred seventy-seven consecutive renal transplant recipients were included. Seventy-seven atherosclerotic events (AE) (12.3%) occurred during a mean follow-up of 7 years. The cumulative incidence of AE increased with the number of human leukocyte antigen (HLA) mismatches (18%, 10%, and 5% in patients with 5–6, 3–4, and 0–2 mismatches, respectively; P =0.012). Human leukocyte antigen mismatch number (hazards ratio, 1.35; 95% confidence interval, 1.10–1.66, for each supplementary mismatch; P =0.005) was an independent risk factor for AE. In the propensity score match analysis, having received a well-matched kidney conferred a reduced risk of AE (hazards ratio, 0.22; 95% confidence interval, 0.05–0.95; P =0.044). We observed a significant correlation between HLA mismatch numbers and circulating CD57 + CD28 − CD8 + T cells (R=0.31; P =0.017). These CD8 + T cells were more frequent in patients with more HLA mismatches ( P <0.0001). Conclusion: Overall, our results suggest that chronic allogeneic stimulation participates to accelerated atherosclerosis observed after transplantation. Abstract : An association among degree of HLA mismatch, increased presence of pro-inflammatory CD57+CD28-CD8+ T cells, and cardiovascular events after renal transplantation suggests that chronic allogeneic stimulation is causal for progression of atherosclerotic disease.